Heidi - Spyri, Johanna (Paignton, England, Ladybird publishers., 1995)
Heidi is happy living on the mountainside with her grandfather, her friend Peter and the goats. But when she is taken to the city to be a companion for frail sickly Clara, she is miserable. Heidi longs to return to the freedom, fresh air and sunshine of the mountains.
Keywords: Children's stories; English fiction